A Meta Analysis – Factors That Influence the Level of Statistical Reasoning of Students in Indonesia - Amelia Destiana; Nurul Astuty Yensy (Universitas Teknokrat Indonesia, 2026)
In today's digital world, Indonesian students face significant challenges with statistical reasoning, a crucial 21st-century skill needed for data interpretation and informed decision-making in academic and daily contexts. To address this educational gap, researchers conducted a comprehensive meta-analysis of 17 empirical studies published from 2012-2024, systematically examining various factors that influence students' statistical reasoning abilities in Indonesia. The study methodically categorized these influences into internal factors stemming from individual student characteristics and external factors related to environmental and instructional elements. The findings revealed that the implementation of Contextual Teaching and Learning (CTL) combined with Realistic Mathematics Education (RME) learning models had the most significant positive impact on enhancing students' statistical reasoning capabilities. These research results provide valuable evidence-based insights for educators, curriculum developers, and policymakers to create more effective educational frameworks and teaching strategies that can substantially enhance statistical literacy among Indonesian students, ultimately improving their capacity for data-driven decision-making in both formal educational settings and practical real-world applications.